Is There an Informal Employment Wage Penalty in Egypt? - Aysit Tansel; Halil Ibrahim Keskin; Zeynel Abidin Ozdemir (Institute for the Study of Labor (IZA), 2015)
This paper considers the private sector wage earners in Egypt and examine their wage distribution during 1998-2012 using Egyptian Labor Market Panel Survey. We first estimate Mincer wage equations both at the mean and at different quantiles of the wage distribution taking into account observable characteristics. Then we make use of the panel feature of the data and estimate models taking into account unobservable characteristics. We also consider the possibility of nonlinearity in covariate effects and estimate a variant of matching models. In all cases we find a persistent informal wage penalty in the face of extensive sensitivity checks. It is smaller when unobserved heterogeneity is taken into account and larger at the top than at the bottom of the conditional wage distribution. We also examine the informal wage penalty over time during the study period and in different groups according to experience and education. The informal wage penalty has increased recently over time and is larger for the better educated but smaller for the more experienced.
Keywords: J21; J31; J40; O17; 330; formal and informal wage gap; formal and informal employment; panel data; Egypt